A comparative study of tactile perception in blind and sighted subjects - Kumari, Sweta; Bankey, Naveen; Shah, Rajesh; Naghate, Gopal (National journal of physiology, pharmacy and pharmacology, 2022)
Background: Blind people are underprivileged from visual experience and visual imaginary that result them to become more dependent on haptic system for the job of tactile perception. Thus, the self-guided tactile investigation in blind individuals enables them to recognize the shapes more rapidly than the sighted counterparts. Aim and Objectives: The aim of the study was to see the increased tactile perception among the blind than the blind folded sighted subjects. Materials and Methods: The study was carried out on 150 blind and 181 blindfolded sighted subjects. In this, each subject was instructed to arrange the aluminum oxide abrasive sand papers of different grit size having grade 60, 80, 100, 120, 140, 200, 240, 360, 400, and 600 from rough to smooth as fast and accurate as possible in seconds to express the functions of haptic sense. Results: The present study showed that the blind subjects had outperformed in terms of speed and accuracy of tactile perception. Conclusions: Lack of vision among blind individuals enables their brain to enhance the sense of vision and the previous tactile exposure and memories along with their regular practice enhance the touch perception in terms of speed and accuracy.